Phubbing Phenomenon in Education: Descriptive Study in SMA Negeri 3 Banda Aceh - Dea Eka Safitri; Sudrajat Sudrajat (Naradidik: Journal of Education and Pedagogy, 2026)
The phenomenon of phubbing as a behavior of ignoring face-to-face interactions because of the focus on smartphones is increasingly prominent in the world of education, especially among secondary school adolescents. The high intensity of digital technology use has the potential to affect the quality of social interaction and the learning process at school. This study aims to describe in depth the phenomenon of phubbing in education among students of SMA Negeri 3 Banda Aceh, as well as identify its characteristics, causative factors, and implications for social interaction and learning. This research uses a descriptive qualitative approach with a literature study method. Data were obtained through searching scientific articles, theses, and research reports from various online databases with inclusion criteria published in 2020-2025 which are relevant to the context of secondary education. Data analysis was carried out through reduction, categorization, and synthesis of literature findings which were then contextualized with the conditions of SMA Negeri 3 Banda Aceh. The results showed that phubbing in students is influenced by the intensity of social media use, fear of missing out (FoMO), low self-regulation, and a digital environment that supports unlimited connectivity. This behavior has an impact on reducing the quality of social interactions, reducing academic engagement, and potentially weakening communication ethics in the school environment. It is concluded that phubbing is a social and pedagogical phenomenon that requires a comprehensive response through strengthening digital literacy, regulation of smartphone use, and character education based on social values and school culture.